Atomic layer deposition of transition metal films and nanostructures for electronic and catalytic applications. Issue 5 (3rd September 2021) - Maina, James W.; Merenda, Andrea; Weber, Matthieu; Pringle, Jennifer M.; Bechelany, Mikhael; Hyde, Lachlan; Dumée, Ludovic F.
Abstract: Atomic layer deposition (ALD) has emerged as the technique of choice in the microelectronics industry, owing to its self-limiting nature, that allows conformal film deposition in highly confined spaces. However, while the ALD of metal oxide has developed dramatically over the past decade, ALD of pure metal, particularly the transition metals has been developing at a very slow pace. This article reviews the latest development in the ALD of pure transition metals and alloys, for electronic and catalytic applications. In particular, the article analyzes how different factors, such as the substrate properties, deposition conditions, precursor and co-reactant properties, influence the deposition of the metal films and nanostructures, as well as the emerging applications of the ALD derived transition metal nanostructures. The challenges facing the field are highlighted, and suggestions are made for future research directions.